Aplikasi Metode Markov Chain untuk Meningkatkan Tingkat Persediaan Bahan Baku yang Optimal - Umar Wiwi Wahyu Eni Maryati (Jurnal Teknik Industri, 2000)
Organize company  stocks,  it's very important  thing  that  company  must be done, because operation cost is depend on how company organize their stock. And lock of stock it's  can anoycny  an such as production  at activities  company.  PT. Domusindo  Perdana  is  a company that  makes product such  as furniture to  full  fill consument  needed.  That  company  must  be ready  stock  one's of their produck  because  they  can't guess  wahat  consument . Want's  it's  can  makes  a  level  of stock  hot optimal  depend  on  this  phenomena,   on  this  thesis  will  explain  a  production  that  using  the  right methode  that  finally  can  calculate  stock  at  company  that  will  be  asking  with  consument  and for calcuiate cost of stock, it's will be using Markov Chain methode.